Colorimetric dual DNAzyme reaction triggered by loop-mediated isothermal amplification for the visual detection of Shiga toxin-producing Escherichia coli in food matrices - Alaa H. Sewid; Joseph H. Ramos; Haley C. Dylewski; Gillian I. Castro; Doris H. D’Souza; Shigetoshi Eda (PLoS ONE, 2025)
Shiga toxin-producing Escherichia coli (STEC) is causing outbreaks worldwide and a rapid detection method is urgently needed. Loop-mediated isothermal amplification (LAMP) has attracted attention in the development of pathogen detection methods; however, current methods for the detection of LAMP amplicon suffer some drawbacks. In this study, we designed a new LAMP method by incorporating peroxidase-mimicking G-quadruplex DNAzyme for a simple colorimetric detection of the LAMP amplicon. As the new method produces LAMP amplicon containing two DNAzyme molecules per amplification unit, the method was termed colorimetric Dual DNAzyme LAMP (cDDLAMP). cDDLAMP was developed targeting 3 common STEC’s virulence genes (stx1, stx2, and eae) that are associated with serious human illnesses such hemorrhagic colitis and hemolytic-uremic syndrome. Immunomagnetic enrichment was used for specific, ultrasensitive, and fast detection of STEC in food samples (leafy vegetables and milk). The sensitivity of cDDLAMP ranged from 1–100 CFU/mL in pure culture to 100–103 CFU/mL in spiked milk, and 104–109 CFU/25g of lettuce. No cross-reaction with other generic E. coli strains and non-E. coli bacteria was observed. The color signal could be observed by the naked eye or analyzed by either UV–Vis spectra or smartphone platforms. Therefore, the cDDLAMP assay is a cost-effective method for detecting STEC strains without expensive machines or extraction methods.